2015
DOI: 10.1007/s11144-015-0885-5
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 1,2-propanediol through glycerol hydrogenolysis on Cu–Al mixed oxides

Abstract: Cu-Al mixed oxides derived from hydrotalcite-like precursors having an atomic ratio of 3:1 and calcined at 300, 400, and 500°C were synthesized. The samples were further reduced under hydrogen atmosphere and its catalytic activity was tested in glycerol hydrogenolysis in a batch reactor. Several techniques such as N 2 physisorption, X-ray diffraction, thermogravimetric analysis, Fourier transform infrared spectroscopy, X-ray photoelectron spectroscopy, scanning electron microscopy, transmission electron micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 42 publications
0
1
0
2
Order By: Relevance
“…Indeed, it has been demonstrated that these catalysts showed a better performance than CuCr 2 O 4 catalysts [154]. In these systems, the activity is a function of the Cu:Al molar ratio [147] and the preparation method. In all cases, the co-precipitation method was used, varying the precipitating agent.…”
Section: Cu Catalystsmentioning
confidence: 99%
“…Indeed, it has been demonstrated that these catalysts showed a better performance than CuCr 2 O 4 catalysts [154]. In these systems, the activity is a function of the Cu:Al molar ratio [147] and the preparation method. In all cases, the co-precipitation method was used, varying the precipitating agent.…”
Section: Cu Catalystsmentioning
confidence: 99%
“…La técnica de coprecipitación también ha sido utilizada para preparar catalizadores de Cu-Al [55,71,72,73,74,75,76,77] y Cu-Fe [78]. Mane et al prepararon catalizadores de Cu-Al encontrando que la presencia de la fase CuAl2O4 y las especies Cu + y Cu 0 determina el éxito en la performance de los catalizadores [72].…”
Section: Cobreunclassified
“…Mane et al prepararon catalizadores de Cu-Al encontrando que la presencia de la fase CuAl2O4 y las especies Cu + y Cu 0 determina el éxito en la performance de los catalizadores [72]. Valencia et al prepararon de forma similar catalizadores de Cu-Al y encontraron que para una relación atómica Cu:Al = 3:1 el rendimiento a 1,2-PG resulta máximo [77].…”
Section: Cobreunclassified